2021
DOI: 10.1155/2021/1723471
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Impact of a Popliteal Plexus Block to Standard Adductor Canal Block in Arthroscopic Anterior Cruciate Ligament Reconstruction: A Randomized Blind Clinical Trial

Abstract: Background. Damage to the anterior cruciate ligament (ACL) is crippling and often requires an arthroscopic outpatient surgery. Nevertheless, many patients experience severe pain during the first day after ACL reconstruction (ACLR). The adductor canal block (ACB) has yielded conflicting results for post-ACLR pain relief. This research investigated the effect of a supplemental popliteal plexus block on postoperative pain outcomes compared to a sole ACB. Methods. Following a randomized design, 60 cases scheduled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…24 Studies have shown that the PPB approach can be applied safely and effectively to cases experiencing ankle and foot operation, minimizing their pain during the procedure . [25][26][27] Li et al highlighted that PPB group had significant reduction in the pain scores for 4 to 16 h postoperatively; the first analgesic requirement, the side effects, and the frequency with which the patient forced the analgesic, were all less. In group PPB, the time to initiate patientcontrolled analgesia (PCA), the first rescue patientcontrolled analgesia time, and the duration of use of an analgesic pump were all longer than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…24 Studies have shown that the PPB approach can be applied safely and effectively to cases experiencing ankle and foot operation, minimizing their pain during the procedure . [25][26][27] Li et al highlighted that PPB group had significant reduction in the pain scores for 4 to 16 h postoperatively; the first analgesic requirement, the side effects, and the frequency with which the patient forced the analgesic, were all less. In group PPB, the time to initiate patientcontrolled analgesia (PCA), the first rescue patientcontrolled analgesia time, and the duration of use of an analgesic pump were all longer than in the control group.…”
Section: Discussionmentioning
confidence: 99%
“…In the PACU, patients in the RA group requires less monitoring time [21, 27], because they had fewer side effects given the absence of GA. They also benefited from prolonged analgesic coverage that spared opioid analgesics [42–45]. As early as 2005, Casati et al [46] did a randomized study of 50 knee arthroscopy cases comparing GA with a dual lumbar plexus and sciatic nerve block.…”
Section: Discussionmentioning
confidence: 99%
“…First, the sample size was small, and the specimens were comprised of cadavers of older age (mean 54 years), which is older than most patients who would need PLT autograft transplantation for ligament reconstruction most commonly following sports injury. Second, the injected watery solution of dyes [19] did not harden and tended to diffuse around the loose, connective tissue under the nerve identified through ultrasound. Third, transducer pressure may have compressed the tissues at the time of ultrasound measurement.…”
Section: Discussionmentioning
confidence: 99%